Al-Ijarah dalam Perspektif Hadis; Kajian Hadis dengan Metode Maudhu’iy - Husain Insawan (Institut Agama Islam Negeri Kendari, 2017)
The purpose of this study was to discover the conception of al-Ijarah in the perspective ofthe hadith; and to know the quality of a hadith which discusses al-Ijarah by first doing naqdal-sanad, naqd al-mart, i'tibar hadith about trustworthiness and his muttabi'an, andgiving syarh (explanation) intact about a representative hadith, so it can serve as a legalumbrella associated with al-Ijarah activities.Using Takhrij al-Hadith bi al-Fazh and Takhrij al-Hadis bi al-Maudhu'iy, this studytraces a number of hadiths and compiles them into a theme; then one of the reperesentativehadiths of the many hadiths that deal with al-Ijarah will be examined more broadly anddeeply.The translations of hadith that are deemed representative are: